ChemInform Abstract: C—H Functionalization of Cyclopropanes: A Practical Approach Employing a Picolinamide Auxiliary. Issue 5 (4th February 2014) - Roman, Daniela Sustac; Charette, Andre B.
Abstract The Pd‐catalyzed C—H arylation of picolinamide‐functionalized cyclopropanes is promoted by either a silver additive or catalytic amounts of pivalic acid in the presence of a carbonate base.